Development of a novel device for monitoring incentive spirometry performance - Aqilah Leela T. Narayanan,; Muhammad Akmal Ayob,; Norayati Nordin,; Arief Ruhullah A. Harris,; Eko Supriyanto, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Lung atelectasis caused by shallow breathing patterns is common after cardiac, thoracic and upper abdominal surgeries. A common method used to address this problem is to encourage patients to perform breathing exercises using incentive spirometers in the postoperative period. However, to be effective, this procedure must be repeated regularly so that adequate lung volumes can be maintained to prevent atelectasis. Current models of single-use, low-cost incentive spirometers do not have features that can track and store data on breathing exercises. This makes it difficult to monitor patients’ breathing exercises effectively. We present here a device designed to be interfaced with the Spiro-ball incentive spirometer and programmed to monitor the incentive spirometry performance. Laboratory based validation performed indicate that there were no significant differences between the value obtained from the device and manual reading; p-value > 0.05 and root-mean-square error (RMSE) is 3.882. The device was able to retrieve and display pertinent data on incentive spirometry performance. It was also able to correctly track and register random sets of inspiration data through different dates and timelines. Being a separate entity which is reusable, it does not add to the cost of the single-use incentive spirometer.